PERANAN CITRA MEREK, HARGA, DAN KEMASAN DIDALAM KEPUTUSAN PEMBELIAN KONSUMEN - William Devrilio Lay; Tina Melinda (Research Center and Case Clearing House PPM School of Management, 2019)
The purpose of this research is to determine the effect of brands, prices, and packaging on Nexfood consumer purchasing decisions. The population used is 108 people from consumers of Nexfood. The number of samples used for this research is 40 people from Nexfood consumers. The variables in this research are brand image (X1), Price (X2), packaging (X3), and purchase decision (Y). The sampling technique in this study used a purposive sampling method. The analysis technique used in this study is multiple linear regression analysis techniques. The results of this research shown that brand image, price, and packaging have a effect on purchases decisions at Nexfood products.